Academic achievement of incarcerated students - Gasa, VG (South African Journal of Higher Education, 2011)
The main function of prison-based education is to prepare the inmates for return to society. Many higher institutions of education that offer distance learning have opened their doors to accommodate prisoners who want to further their studies. Thus far, many prisoners have received bachelor’s degrees from different higher institutions of education in various academic fields. Research was undertaken in an attempt to gain greater understanding of the reasons behind their outstanding or poor academic performance. Both the benefits and the difficulties experienced by prisoners as a result of their academic work were considered. The statistical documents obtained from the University of South Africa’s Department of Information and Strategic Analysis indicated a high pass rate among incarcerated students. On the other hand, the number of those who show poor academic performance, although insignificantly low, cannot be ignored. It indicates a need for support measures such as catering for the diverse needs of incarcerated students.